Fabrication and Characterization of Magneto-Rheological Shear-Stiffened Elastomers - Yang, Jian; Sun, Shuaishuai; Du, Haiping; Alici, Gursel; Yan, Tianhong; Li, Weihua (Frontiers in Materials, 2014)
This study presents a novel smart solid material called magneto-rheological shear-stiffened elastomer whose storage modulus can be changed obviously by both magnetic field and shear rate. The magneto-rheological shear-stiffened elastomer was fabricated by mixing shear-thickening fluids with carbonyl iron particles and silicon rubber thoroughly. All of the samples were then tested by using a parallel plate rheometer. It is noted that increasing strain induces a slight decrease on the storage modulus but an increase on the maximum shear stress of the samples before a critical shear strain. In terms of the Magneto-rheological effect, magneto-rheological shear-stiffened elastomer is more sensitive to the change of magnetic field because it shows a faster increase in storage modulus and the maximum shear stress with growing current levels when compared to magneto-rheological elastomer. The comparison results between different magneto-rheological shear-stiffened elastomer samples reveal that the bigger the mass fraction of shear-thickening fluids the larger the storage modulus when the samples are loaded at a same shear rate. Additionally, the magneto-rheological shear-stiffened elastomer shows an obvious increase on the storage modulus and the maximum shear stress when the shear rate increases.